Open innovation adoption: a Rasch psychometric analysis on technology exploitation / Siti Noratisah Mohd Nafi ... [et al.] - Mohd Nafi, Siti Noratisah; Yusof, Rushami Zien; Thi, Lip Sam; Saad, Rohaizah (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2016)
Open innovation adoption continues to become an issue for high technological companies competing in local and global markets. As open innovation put forward the importance of pulling together the strength of internal and external means of organizations, as it is important to look and dwell into the reasons that will be able to explain the adoption of open innovation. The purpose of this study is to present the test development process that measures the technology exploitation towards open innovation adoption. Rasch measurement model was used for the instruments measurement analysis. Results from the reliability indices, unidimensionality and item-fit analysis exhibited an acceptable and satisfactory measure of the instruments used for measuring technology exploitation. Implication of these tests can be used for placement, diagnostics and predictive assessment purposes.